Kinetic and Thermal Studies of Zn(II) and Cd(II) Diallyldithiocarbamate Complexes with 2,2'-Bipyridine and 1,10-Phenanthroline - Al-Sou'od, K.A.; Ali, B.F.; Al-Refai, M. (Asian Journal of Chemistry, 2010)
In present studies, the synthesis and characterization of mixed-ligand complexes of Zn(II) and Cd(II) diallyldithiocarbamate (aldtc) with 2,2'- bipyridine (bipy) and 1,10-phenanthroline (phen) were reported. The new complexes [M(aldtc)2(NN)]; [M = Zn, Cd; NN = bipy and phen] have been characterized by partial elemental analyses and using IR, 1H and 13C NMR spectroscopy. Thermal decomposition of these complexes was investigated using TG and DTG. The decomposition mechanisms were suggested and rationalized based on the structure of complexes and the nature of intermediate products and final residues. The analysis illustrates that the compounds show slightly different pattern of fragmentation leading to M(S2CNR2)SCN which then decomposes to MS residue. Kinetic analysis of the thermogravimetric data using the methods of Kissinger and Flynn-Wall-Ozawa was also made to evaluate the activation energy of the complexes. Both methods gave almost similar results.